Predicting whistle-blowing intention in Malaysia : evidence from manufacturing companies - Ab Ghani, Nadzri (Curtin University, 2013)
'The world will not be destroyed by those who do evil, but by those who watch them without doing anything' – Albert EinsteinThe function of whistle-blowing as an effective internal control mechanism has been accepted around the globe. Previous whistle-blowing literature includes many studies that have attempted to identify various predictive variables of whistle-blowing intention. However, the results of these studies remain inconclusive. Further, little is known about the underlying mechanism behind the relationships between the predictive variables and whistle-blowing intention.This study intends to advance research by investigating the relationships between several predictive variables (internal locus of control, work experience and ethics training) and whistle-blowing intention among supervisors in Malaysia. Additionally, supported by cognitive moral development theory, this study empirically investigates the mediating effect of ethical reasoning on such relationships.A two-stage sampling technique was applied to randomly collected data from 311 supervisors in large manufacturing companies listed under Bursa Malaysia Berhad. Structural equation modelling software (Analysis of Moment Structures, or AMOS) was applied to examine the direct and mediating effects of posited relationships.Results failed to support hypothesised relationships between both internal locus of control and work experience, and whistle-blowing intention. Only ethics training was statistically significant as a predictive variable for whistle-blowing intention among supervisors in Malaysia. Furthermore, internal locus of control was not significantly related to ethical reasoning. The other two predictive variables (work experience and ethics training), however, were significantly related to ethical reasoning. As hypothesised, ethical reasoning is significantly related to whistle-blowing intention. Findings confirmed that ethical reasoning mediates the relationships between both work experience and ethics training, and whistle-blowing intention.This study makes several theoretical contributions and provides further insights about current the whistle-blowing literature in Malaysia. Methodological and practical implications are discussed and several potential avenues for future research are identified and proposed.